2021
DOI: 10.1002/er.7368
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical properties and thermal performance evaluation of multiwalled carbon nanotube‐based organic phase change materials using T‐History method

Abstract: Experimental studies have been carried out to evaluate the thermophysical properties and thermal performance of thermal energy storage (TES) systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Therefore, different studies have been employed to enhance carbon foam properties. Infiltration carbon foam with phase change material (PCM) was used to improve the foam heat capacity as well as the PCM thermal conductivity 10‐15 . Recently, Meng et al 16 examined the impact laws of porosity and pore density of copper foam to improve the thermal performance of the composite of paraffin‐metal foam PCM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, different studies have been employed to enhance carbon foam properties. Infiltration carbon foam with phase change material (PCM) was used to improve the foam heat capacity as well as the PCM thermal conductivity 10‐15 . Recently, Meng et al 16 examined the impact laws of porosity and pore density of copper foam to improve the thermal performance of the composite of paraffin‐metal foam PCM.…”
Section: Introductionmentioning
confidence: 99%
“…Infiltration carbon foam with phase change material (PCM) was used to improve the foam heat capacity as well as the PCM thermal conductivity. [10][11][12][13][14][15] Recently, Meng et al 16 examined the impact laws of porosity and pore density of copper foam to improve the thermal performance of the composite of paraffin-metal foam PCM. Their results showed that decreasing the porosity might improve the thermal behavior of the composite mainly between 92% and 98%.…”
mentioning
confidence: 99%
“…Nano-enhanced phase change materials (NEPCM) are usually indicated modified thermophysical properties in addition to the thermal conductivity like viscosity, specific heat capacity, and latent heat. 13 Nanoparticles with high thermal conductivity are commonly incorporated in PCM with a lower concentration ratio (CR) of 5%. Although increasing the nanoparticle amount provides higher thermal conductivity of NEPCM, an upper limit for CR has been reported typically.…”
mentioning
confidence: 99%